Application and prospects of genetic engineering in CAR-NK cell therapy - Hu, Caidong; Lai, Wenhong; Tian, Bin; Xu, Xi; Xie, Shuiling; Zhong, Wenting; Kang, Huiqiang; Chen, Xiaoyun; Li, Hailiang; Xu, Jingxin; Liu, Liping (Frontiers in Immunology, 2025)
With the rapid advancement of genetic engineering technologies, CAR-NK cell therapy, as an emerging immunotherapeutic approach, has demonstrated significant potential. CAR-NK cells recognize and eliminate tumor cells through chimeric antigen receptors (CARs). Genetic engineering techniques have enhanced the targeting and anti-tumor activity of CAR-NK cells by optimizing key components of the CAR structure, such as signal peptides, single-chain variable fragments (scFvs), linkers, and hinge regions. Additionally, NK cells can be derived from diverse sources, including peripheral blood, umbilical cord blood, stem cells, and NK cell lines, each with its unique advantages and limitations. Although CAR-NK cell therapy has shown promising anti-tumor efficacy in preclinical studies, it still faces numerous challenges. In the future, further optimization of CAR-NK cell design through genetic engineering and overcoming the immunosuppressive tumor microenvironment will be crucial for enhancing its clinical application efficacy. This review will comprehensively discuss the current applications, technical challenges, and future directions of genetic engineering in CAR-NK cell therapy.